Proceedings of the 22nd ACM International Conference on Information &Amp; Knowledge Management 2013
DOI: 10.1145/2505515.2505625
|View full text |Cite
|
Sign up to set email alerts
|

Recommending tags with a model of human categorization

Abstract: When interacting with social tagging systems, humans exercise complex processes of categorization that have been the topic of much research in cognitive science. In this paper we present a recommender approach for social tags derived from ALCOVE, a model of human category learning. The basic architecture is a simple three-layers connectionist model. The input layer encodes patterns of semantic features of a user-specific resource, such as latent topics elicited through Latent Dirichlet Allocation (LDA) or avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
(40 reference statements)
2
25
0
Order By: Relevance
“…For instance, in a recent work, Seitlinger, Kowald, Trattner, and Ley (2013) have emulated the gist-based production of tags as a simple connectionist model and demonstrated that a tag recommender based on this model provides more accurate recommendations than a well-established latent Dirichlet allocation approach.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a recent work, Seitlinger, Kowald, Trattner, and Ley (2013) have emulated the gist-based production of tags as a simple connectionist model and demonstrated that a tag recommender based on this model provides more accurate recommendations than a well-established latent Dirichlet allocation approach.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a recent study [28], we introduced a mechanism by which memory processes involved in tagging can be modeled on two levels of knowledge representation: on a semantic level (representing categories or LDA topics) and on a verbal level (representing tags). Next, we will aim at combining this integrative mechanism with the BLL equation to examine a potential interaction between the impact of recency (time-based forgetting) and the level of knowledge representation.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on social tagging systems for our study not only because their datasets are freely-available for scientific purposes but also because tagging data can be easily utilized to derive semantic topics for resources from it [17] by means of Latent Dirichlet Allocation (LDA) [25]. This initial step was necessary since our datasets did not contain categories or topics for the resources (e.g., like Wikipedia categories, see [35]) that are the basis for our approach. Thus, we chose LDA to simulate this external categorization.…”
Section: Datasetsmentioning
confidence: 99%